(3GdCfhGQaj GdLeY Hjf GdeJbi hGdGSJPcGQ TQMi GdehWC dGHf GdhdjO GdHGLi hGHf YeQHf YHO GdHQs - (3CHh YHO Gddg eMeO Hf SYjO Hf CMeO GdCfUGQj, GHf RQbhf,J (B586 (3g` s
(3ChdgG (B:s
(3GdbVGA ai GdYeQi (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3CjeG QLd CYeQ dg hdYbHI aEfgG ddPi jYWGgG GdMOjK s
(3BNQgG (B:s
(3HHGH eG jcQg ef GdUObI hTQM bhd QShd Gddg Udi Gddg Ydjg hSde dG JMd GdUObI dBd eMeO s
(3GdefJbi hGdCSJPcGQ hQO GdYfhGf GdCUdi ai c X (B2 / 1907s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B139s
Keywords: (3GdMOjK h GdeUWdMs